Pengembangan Desa Wisata Melalui Community Based Tourism di Kabupaten Kepulauan Sangihe - Roosalina Hera Lucia; Oktavianus Wayan Semuel; Steven Yones Kawatak; Prijanto Familia Benedichta (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Tourists have very varied desires, which is why tourist villages are formed to introduce tourists more about the communities within them and the resources that support them. Of course, every tourism management is very dependent on the existence of human resources through Community Based Tourism. Promising that human resources around tourism areas can be more independent in managing and developing existing destinations. Apart from that, human resources who have new competencies and are capable of managing a tourist destination will become more innovative and creative to adapt to developments in tourism management. Likewise with the Para Lelle tourist village in Sangihe Islands Regency which has various destinations and is a leading tourist village, that there are still operational obstacles in the form of electricity problems and inadequate and optimal internet networks, as well as transportation which depends on weather factors. This research uses a qualitative research method with a descriptive approach to see how human resources develop with limited facilities such as the problems mentioned above. Based on the research results, several reality phenomena were found, such as tourism activities which are managed by the community independently and studied based on economic, social, cultural and environmental dimensions so that we get interrelated results in assessing strengths and weaknesses for SWOT analysis, then there are recommended strategies for developing resources. humans and the Lelle Tourism Village.